ELECTRONIC EDUCATIONAL RESOURCES FOR ENTREPRENEURIAL TRAINING OF FUTURE SPECIALISTS - Banit, Yury S. (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article presents the author's generalization about the specifics of entrepreneurial training of future economists in the conditions of educational and business relocations in modern conditions in Ukraine, taking into account development trends and the importance of socially (community) oriented education. Certain aspects of the use of electronic educational resources for business education and the formation of entrepreneurial competence are highlighted.